Delayed-immediate breast reconstruction: An assessment of complications and outcomes in the context of anticipated post-mastectomy radiotherapy. (February 2023) - Cuffolo, Giulio; Pandey, Ayushi; Windle, Rebecca; Adams, Titus; Dunne, Nicola; Smith, Brendan
Summary: Introduction: The detrimental effects of post-mastectomy radiotherapy on breast reconstruction are well known. We report our experience with a delayed-immediate approach involving an initial subcutaneous implant with definitive reconstruction after adjuvant radiotherapy. Methods: Patients were identified retrospectively from hospital, theatre and implant registry records. Details regarding demographics, cancer pathology, surgical data and oncological therapies were collected. Primary outcomes included complication rates of first-stage surgery and time to definitive reconstruction. Results: A total of 115 patients underwent mastectomy and temporary subcutaneous implant (36 nipple sparing) between 2008 and 2019. Five were smokers with eleven having a body mass index > 30. The median age was 46 years (27–76 years) and tumour size 50 mm. Almost 95% underwent radiotherapy, 82% chemotherapy and 70% had axillary node clearance. Median mastectomy weight was 464 g (123–1300 g) with median temporary implant volume 375 cc (180–655 cc). Complications of first-stage surgery at three months included 5.2% implant loss ( n = 6), 14.8% infection rate, 17.4% readmission rate and 10.4% returned to theatre. Reconstructive failure occurred in four cases (3.5%). A total of 76 patients completed definitive reconstruction, including 26 autologous, 21 latissimus dorsi with implant, and 28 implant-only reconstructions. The median time to reconstruction following the completion of radiotherapy was 12 months. This increased in those who had implant complications (28 vs. 15 months) or radiotherapy (16 vs. 10 months) versus those without. Conclusions: Delayed-immediate breast reconstruction using a temporary subcutaneous implant has been shown to be a safe, feasible and potentially beneficial method than simple mastectomy and delayed reconstruction with a complication rate comparable to that of immediate implant reconstruction.